Penggunaan Google Workspace untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Daring - Erna Rahayu (Jurnal Pendidikan Madrasah, 2021)
This study aims to improve the students’ achievement and involvement during the online learning by using the applications of Google Workspace. The subjects of the research were the students of grade 9B of MTs Negeri 1 Bantul in the academic year 0f 2021/2022. The research implemented the stages of Class Action Research through two cycles that include planning, implementing, observing, and reflecting activities. The result showed that the use of Google Workspace is able to improve the students’ achievement and involvement in the online learning. The improvement of students’ achievement can be seen from the increasing of the mean of evaluation which was 77,5% on Cycle 1 and 84% on Cycle 2. There was also increasing on the number of students who are able to exceed the passing grade that was 76% on Cycle 1 and 82.1% on Cycle 2. The students’ involvement is also improved. The numbers of students involved in Cycle 1 and Cycle 2 were 81.3%.